Raegan Matthews SHP Final - Matthews, Raegan (East Carolina University, 2021)
Sensory Processing Disorders affect 5-16% of school aged children. In addition, 40% of children with ADHD also share the Sensory Processing Disorder. Furthermore, sensory deficits are prominent in the learning environment and hinders many students from reaching their full potential. SENSE-ational began as an Honors 2000 team at East Carolina University with the goal of helping reduce distractions in the classroom for students with sensory processing issues. Our original idea was to design, create, and manufacture kits that were to be distributed into those very classrooms. Due to COVID-19, and the lack of children in the classroom, we were unable to implement these kits. We needed to pivot in our attempt to help children who were struggling with online learning. We produced “DIY” YouTube videos of how to make sensory items. We now have a handful of quality, engaging, and useful videos on our YouTube channel, as well as our very own logo and a plan to move forward with our brand. We are utilizing the 3D printers in the Innovation and Design Lab at ECU to create and test our prototypes. In the future, we plan to donate all of our new designs to community schools here in Pitt County, so that our work throughout this project can have an impact on the children of Greenville, North Carolina. This will hopefully improve access to sensory items, and increase focus and learning for the kids of this community. In addition, we hope it will serve as a way for teachers and parents to view the benefits of sensory items in everyday school environments.
Keywords: Sensory; development